The Freedom of Scientific Research in International Law: Outer Space, the Antarctic and the Oceans. - Graham, Gerald (University of Geneva, 1981)
This 1980 doctoral dissertation from the Graduate Institute at the University of Geneva in Geneva, Switzerland examines the international legal regime for the conduct of scientific research in three areas that are, in a sense, beyond national jurisdiction- those three areas being outer space, the Antarctic and the oceans. It does so by looking at: general principles regulating the use of the three areas; fundamental rules relating specifically to scientific research; limitations on the freedom or right to conduct scientific research; specific obligations as they pertain to scientific research activities; and miscellaneous rules. The Thesis ends with a series of conclusions that are gleaned from the treaties, case law and practice that are examined in the body of the Thesis. PhD Bound copies of this dissertation are also available, at a cost of $50 USD to cover the cost of printing and binding one copy, plus shipping costs. Please provide shipping details when ordering, including the name of a recipient to be placed on the envelope label, for tracking purposes and to acknowledge receipt.